Effect of Short-term Probiotic Yogurt Consumption on Caries Risk Factors in Infants - Ece Eden; Aslı Topaloğlu; Funda Özgenç; Güzide Aksu; Ecem Ergin (Galenos Yayinevi, 2019)
Aim:We aimed to evaluate the effect of short-term probiotic yogurt consumption on pH, buffering capacity, and Streptococcus Mutans, Lactobacilli and secretory immunoglobulin A (sIgA) levels in saliva of 6-8 months old healthy infants.Materials and Methods:Twenty healthy infants and their mothers were enrolled in the study. They were randomly allocated into two groups as study and control. In the study group, probiotic yogurt (Bifidobacterium Longum BB536, Bifidobacterium Bifidum Bb12, Lactobacillus Rhamnosus HN001) was given to infants for 3 weeks whereas, in the control group, home-made yogurt was consumed. A dental saliva pH-Indicator strip (GC, Japan) was used for salivary pH measurements. Buffering capacity was determined using CRT buffer (Ivoclar Vivadent, Liechtenstein). The counts of salivary mutans streptococci and lactobacilli were evaluated using CRT bacteria (Ivoclar Vivadent,Liechtenstein). ELISA was used for sIgA. Scores at baseline and three weeks after were statistically evaluated by Wilcoxon test using the IBM SPSS 20.0 program.Results:Salivary pH, IgA, S. mutans and lactobacilli values showed no significant change after 3 weeks of probiotic yogurt consumption, however there was a statistically significant increase in the buffering capacity of saliva (p=0.04).Conclusion:Short-term probiotic yogurt intervention in infants during the early stages of life might have benefits for oral health. Further studies with both short- and long-term use of probiotics must be implemented in infants to confirm the results and see the effects on other caries risk factors.